Geophysical investigation of the mineral prospect on the Wortel Farm, Namaqua Belt, Northern Cape, South Africa - Buthelezi, Minenhle (My University, 2020)
The Wortel Farm no. 42 is one of many areas in the Namaqua metamorphic terrain with mineral occurrences whose source, potential and extent have not been investigated. Mapped copper and tungsten mineral occurrences are identified on the farm, sitting on the Koeipoort granite of the Kheisian Period (~2.0 Ga); gneisses, schist, shale, amphibolite and quartzites of the Bushmanland Group and intruding dykes and sheets of the Gareskop Suite. The farm is located 20 km north of the well-known Aggeneys base metal sulphide deposits and 120 km north-east of the O’kiep copper district, all consisting similar lithologies with minor variations. This research was aimed at investigating (and delineating) the potential of the copper occurrence on the farm using multiple geophysical techniques. Gravity, aeromagnetic, DC resistivity and magnetotelluric methods were chosen to map the geology framework, both spatially and in depth, and induced polarization (IP) technique was used for the direct targeting of the mineralisation. The Namaqua Sector of the Namaqua-Natal Mobile Belt, which is composed of low-to-high metamorphic grade rocks, experienced orogenic deformations that occurred between 2.0 – 0.95 Ga, resulting in strongly metamorphosed, overturned and deformed sequences, with a wide a range of mineral occurrences across the sector (only partially investigated). Based on outcrop mapping and geophysical data interpretation, five previously unidentified faults at least 200 m long, and striking E-W, NW and NE, were identified in the various lithologies. Multiple folds were also mapped on surface through dip measurements and inferred from interpretations of the geophysical data and they ranged in strike length between centimetres and kilometres. The geochemical analyses showed that the study area has elevated concentrations of Cr, Co, Cu, Fe, Li, Mg and Ni elements. Aeromagnetic data collected at 80 m flight height and 200 m line spacing were interpreted and modelled with the PyGMI software written in Python. The IP data were acquired over the high magnetic amplitude anomaly. A 2 km x 600 m zone of high magnetism (26380 nT or -265 nT with IGRF removed) is spatially coincident with parts of a 8 – 11 mV/V chargeability anomaly which is also correlated with the mapped Gareskop Suite dykes and Koeipoort granite. The high chargeabilities were interpreted as a possible source of the geochemical elements. A resistivity anomaly (4 km x 500 m) coincides with most of the elevated chargeability anomaly, with a similar N-S strike and distribution. This is interpreted as an indicator that the possible mineral occurrence is structurally bound across granites, dykes and sand cover unlike the Aggeneys sulphide deposits that are strata-bound in the Gams Formation. Although Aggeneys and Wortel Farm are 20 km apart with minor differences in lithology their mineral occurences are different in nature: Aggeneys stratabound in Gams Formation and Wortel structurally bound. The mapped geochemical anomalies and occurrences are hosted within the high chargeability zones. The structural confinement of these anomalous features indicate the source(s) of these mineral occurrences are of a pervasive nature as seen in the Springbok vicinity that the Namaqua region was subjected to mineralising fluids of post Namaqua age and yet unknown source. The porphyry system is inferred to be most probable mineralising system, occurring in and around the Gareskop Suite rocks. Interpretation of magnetotelluric data revealed dome-like resistive crustal segments, shearing, folding, thrusting and faulting that may have been pathways for the mineralising hydrothermal fluids and attributed to the final deposition and preservation of the mineralisation. Geology structures are well defined by the gravity data. From a palaeomagnetic study of the rocks surrounding the interpreted mineral occurrence both positive and negative inclination directions were obtained and discounting the effects of induced thermal remanence due to lightning strikes, is interpreted as that the rocks were magnetised at different times. As such a positive magnetic declination of the rocks indicates that the sampled rocks were magnetised when the magnetic north was to the east of the geographic north. This research indicate that the Namaqua sulphide mineral deposits can occur in various forms even in areas with similar lithologies and close proximity, like the Wortel Farm and Aggeneys area. The nature of the Wortel Farm deposit resembles a magmatic segregation of disseminated sulphides while the Aggeneys deposit is of a SEDEX nature, based off the chargeability anomalies of similar amplitudes mapped as separate bodies coinciding with the amphibolite dykes. The geophysical methods chosen for the investigation successfully mapped the subsurface structure with great detail, and delineated the lateral extent of the possible mineralisation. The integration of different geophysical datasets proved crucial and a necessity and complemented other datasets (geology and geochemistry) to highlight various geological details that are required to delineate a base metal deposit in a complex metamorphic terrain
A dissertation submitted to the Faculty of Science in fulfilment of the requirements for the degree of Master of Science, School of Geoscience, University of the Witwatersrand, Johannesburg, 2020
Keywords: Geomorphology--South Africa; Geology